In vitro organogenesis from internodal segments of adult sweet orange plants - Bassan, Meire Menezes; Mourão Filho, Francisco de Assis Alves; Miyata, Luzia Yuriko; Mendes, Beatriz Madalena Januzzi (Pesquisa Agropecuaria Brasileira, 2011)
The objective of this work was to optimize in vitro plant regeneration via organogenesis from tissues of adult 'Hamlin', 'Pêra', and 'Valência' sweet orange plants. Explants were grown in EME culture medium with different concentrations of 6-benzylaminopurine (BAP) and naphthaleneacetic acid (NAA), at 27ºC in the absence of light for 50 days, followed by a 16-hour photoperiod for 20 days. Regeneration was assessed 50 and 70 days after in vitro culture. Organogenesis in cultivars Hamlin and Valência was promoted by EME supplemented with BAP, while NAA showed no apparent effect.